“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Über die Abgrenzung von Auflösungskonzepten in der industriellen Computertomografie - Binder, Felix; Hausotte, Tino (tm - Technisches Messen)
Unter dem Begriff der Auflösung wird für gewöhnlich das kleinste messbare Merkmal eines Messsystems verstanden. In der dimensionellen Computertomografie hingegen haben sich in den vergangenen Jahren mehrere Auflösungskonzepte etabliert, die aufgrund der fehlenden Normung zueinander im Kontrast stehen. In diesem Beitrag werden die drei häufigsten Konzepte, die Voxelgröße, die Ortsauflösung und die metrologische Strukturauflösung in Kürze vorgestellt. Anschließend wird eine Abgrenzung zwischen den Konzepten getroffen und ein Integration der bestehenden Konzepte in ein gemeinsames Amplituden-Wellenlängen Diagramm diskutiert.
Keywords: Electrical and Electronic Engineering; Instrumentation

Herausforderungen bei computertomografischen Untersuchungen von Fügeverbindungen - Busch, Matthias; Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Die Erkennbarkeit von Rissen und geometrischen Qualitätskennwerten von Fügeverbindungen mittels Computertomografie ist von der Interfacestrukturauflösung abhängig, welche mittels geeigneter Prüfkörper untersucht wird. Die Reduktion von Abbildungsartefakten im Bereich von Bauteilzwischenräumen und -oberflächen verbessert deren dimensionelle Erfassbarkeit.
Keywords: Electrical and Electronic Engineering; Instrumentation

Lamb wave based approach to the determination of acoustic material parameters - Johannesmann, Sarah; Claes, Leander; Feldmann, Nadine; Zeipert, Henning; Henning, Bernd (tm - Technisches Messen)
Abstract In this paper a measurement procedure to identify viscoelastic material parameters of plate-like samples using broadband ultrasonic waves is presented. Ultrasonic Lamb waves are excited via the thermoelastic effect using laser radiation and detected by a piezoelectric transducer. The resulting measurement data is transformed to yield information about multiple propagating Lamb waves as well as their attenuation. These results are compared to simulation results in an inverse procedure to identify the parameters of an elastic and a viscoelastic material model.
Keywords: Electrical and Electronic Engineering; Instrumentation

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Investigating peculiarities of piezoelectric detection methods for acoustic plate waves in material characterisation applications - Claes, Leander; Schmiegel, Hanna; Grünsteidl, Clemens; Johannesmann, Sarah; Webersen, Manuel; Henning, Bernd (tm - Technisches Messen)
Acoustic waves in plates have proven a viable tool for testing and material characterisation purposes. There are a multitude of options for excitation and detection of theses waves, such as optical and piezoelectric systems. While optical systems, with thermoelastic excitation and interferometric detection, have the benefit of being contactless, they usually require rather complex and expensive experimental setups. Piezoelectric systems are more easily realised but require direct contact with the specimen and usually have a limited bandwidth, especially in case of piezoelectric excitation. In this work, the authors compare the properties of piezoelectric and optical detection methods for broad-band acoustic signals. The shape (e. g. the displacement) of a propagating plate wave is given by its frequency and wave number, allowing to investigate correlations between mode shapes and received signal strengths. This is aided by evaluations in normalised frequency and wavenumber space, facilitating comparisons of different specimens. Further, the authors explore possibilities to utilise the specific properties of the detection methods to determine acoustic material parameters.

Modelling damping in piezoceramics: A comparative study - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The progress in numerical methods and simulation tools promotes the use of inverse problems in material characterisation problems. A newly developed procedure can be used to identify the behaviour of piezoceramic discs over a wide frequency range using a single specimen via fitting simulated and measured impedances by optimising the underlying material parameters. Since there is no generally accepted damping model for piezoelectric ceramics, several mechanical damping models are examined for the material identification. Three models have been chosen and their ability to replicate the measured impedances is evaluated. On the one hand, the common Rayleigh model is considered as a reference. On the other hand, a Zener model and a model using complex constants are extended to model the transversely isotropic material. As the Rayleigh model is only valid for a limited frequency range, it fails to model the broadband behaviour of the material. The model using complex constants leads to the best fit over a wide frequency range while at the same time only adding three additional parameters for modelling damping. Thus, damping can be assumed approximately frequency-independent in piezoceramics.

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Inverse piezoelectric material parameter characterization using a single disc-shaped specimen - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The increasingly simulation-driven design process of ultrasonic transducers requires several reliable parameters for the description of the material behaviour. Exact results can only be achieved when a single specimen is used in the identification process, which typically is prone to the problem of low sensitivities to certain material parameters and thus high uncertainties. Therefore, a custom electrode topology for increased sensitivity is proposed for a piezoceramic disc. The thereupon conducted measurements of the electric impedance can be used as a starting point for an inverse approach where an equivalent simulation model is used to identify fitting material parameters. An optimisation strategy based on a preliminary sensitivity analysis is presented that leads to a good agreement between measurement and simulation. Furthermore, the proposed measurement procedure is able to evaluate the quality of the simulation model. Hence, different frequency-dependent damping models are presented and evaluated.

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Acoustic absorption measurement for the determination of the volume viscosity of pure fluids / Messverfahren für die akustischen Absorption zur Bestimmung der Volumenviskosität reiner Fluide - Claes, Leander; Hülskämper, Lars Moritz; Baumhögger, Elmar; Feldmann, Nadine; Chatwell, René Spencer; Vrabec, Jadran; Henning, Bernd (tm - Technisches Messen)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

An acoustic waveguide-based approach to the complete characterisation of linear elastic, orthotropic material behaviour - Johannesmann, Sarah; Düchting, Julia; Webersen, Manuel; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Continous-fibre reinforced plastics; material parameters; orthotropy; ultrasonics

Viskoelastizität und Anisotropie von Kunststoffen: Ultraschallbasierte Methoden zur Materialparameterbestimmung - Bause, Fabian; Claes, Leander; Webersen, Manuel; Johannesmann, Sarah; Henning, Bernd (tm - Technisches Messen)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Uncertainty estimation for linearised inverse problems comparing Bayesian inference and a pseudoinverse approach for acoustic transmission measurements - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Luftultraschall-Abstandsmessung mit digitaler Signalverarbeitung zur Verkürzung des Mindestabstandes - Schröder, Andreas; Henning, Bernd (tm - Technisches Messen)

Geführte akustische Wellen zur Flüssigkeitscharakterisierung - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)